Edukasi Literasi Keuangan dalam Membangun Fondasi Investasi Dini - Leisthari, Fepi; Handayani, Tika; Sunanto, Sunanto; Aprini, Hidayah; Suharmanto, Ardelia; Napitupulu, Rizal Afif A.; Yogasnumurti, Raras Risia (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Financial literacy education should ideally be introduced from an early age during school years. Children need to be guided and accustomed to good financial behaviors. This community service research aims to evaluate the effectiveness of financial literacy education in fostering an early investment foundation among students of SMK Muhammadiyah Pangkalan Balai. The low level of financial literacy among the younger generation, particularly in the context of investment, remains a relevant challenge amidst the dynamics of the digital economy. Employing interactive socialization and counseling methods, this program involved 65 twelfth-grade students. Pre-test and post-test results showed a highly significant increase in knowledge (average gain score of 35.8 points), accompanied by positive changes in students' attitudes and interest in early investment. The program's novelty lies in its emphasis on "financial adaptability" and the integration of entrepreneurial values. It is concluded that financial literacy education with an interactive counseling approach is highly effective in equipping students of SMK Muhammadiyah Pangkalan Balai with practical financial competencies for the future.